A patient with long-term diabetes dies following infection with Francisella novicida in Guangdong province, China: a case report - Linjin Fan; Jialong Guan; Lizhi Feng; Yulong Wang; Huimin Zeng; Ying Zhu; Hao Li; Qiang Chen; Linghua Li; Jun Qian; Linna Liu; Yueping Li; et al. (​​​​​​​​Infectious Diseases & Immunity)
Abstract. The rarity of Francisella novicida infection in humans is well-known, and the F. novicida cases occur in immunocompromised patients or those with underlying health problems. Herein, we report the case of a patient with long-term diabetes who died following F. novicida infection that caused multiple organ failure, although F. novicida was effectively eliminated using antimicrobial therapy. Microbiological confirmation of F. novicida infection relies on metagenomic next-generation sequencing (mNGS) and pdpD-2 gene-specific identification. This study highlights the importance of early pathogen diagnosis in severely infected patients, particularly in cases of F. novicida, and indicates that mNGS is a useful tool for early diagnosis.